Utilization of the flow ratio measured by echocardiography (FRecho) compared to the flow ratio by right heart catheterization (FRrhc) for detecting Eisenmenger syndrome in uncorrected acyanotic adult congenital heart disease (ACHD) - Charlotte Johanna Cool; Achmad Fitrah Khalid; Norman Sukmadi (BMC Medical Imaging)
Abstract Background The increasing number of adult congenital heart disease (ACHD) patients, especially in low- and middle-income countries (LMICs), necessitates effective management methods. The Qp/Qs or flow ratio (FR) is crucial for this purpose because one of the indications for closure is a significant shunt. This study compares the utility of the transthoracic echocardiography (TTE)-derived flow ratio (FRecho) with that of the right heart catheterization (RHC)-derived flow ratio (FRrhc) to guide clinical decisions in resource-limited settings. Materials and methods This cross-sectional study in Bandung, Indonesia, included 36 patients with uncorrected acyanotic ACHD who underwent both RHC and TTE on the same day. FRecho was calculated using stroke volumes of the respective ventricles derived from Doppler measurements, and FRrhc was measured using indirect Fick’s method. Results Of the 36 patients, 80.6% were female, with a median age of 31 (18–65) years. The majority had secundum atrial septal defects (61.1%). The mean FRecho was 2.8 ± 1.5 and the median FRrhc was 1.69 (0.46–3.89). FRecho showed a significant positive correlation with FRrhc (ρ = 0.656, p < 0.001). Bland‒Altman analysis revealed a mean difference of 1 (-1.4–3.3). Subgroup analysis of patients with a FRrhc shunt < 1 showed a mean difference of 0.7 (-1–2.3). Conclusion TTE-derived FRecho tends to overestimate FR compared to FRrhc. FRecho should not be used as a surrogate for FRrhc in this population.